The Role of Relationship Marketing, and Satisfaction As Variable Mediation: Study at Bank BPR UMKM East Java in Surabaya - Panjaitan, Hotman; Laely, Nur (International Review of Management and Marketing, 2017)
This paper discusses the causal relationship between relationship marketing, service quality, customer satisfaction, and customer loyalty of Bank BPR UMKM East Java in Surabaya. One model is proposed to examine the role of relationship marketing, and satisfaction as a mediation variable on indirect relationship of service quality, relationship marketing and loyalty. The population in this research is the customer of BPR Bank of UMKM East Java in Surabaya. From the test results in the model in this study, with Maximum Likelihood Estimation (MLE), structural equation model analysis (SEM), convenience sampling method and software Amos 22, on 160 respondents. The results showed that the research model was accepted with determinant coefficient (R2) of 90.7%. Research also shows that service quality influences relationship marketing, and customer satisfaction. Service quality has no significant effect on customer loyalty. Relationship marketing affects customer satisfaction and customer loyalty. Customer satisfaction affects customer loyalty. Customer satisfaction is a positive mediation variable on the relationship of service quality with loyalty. Relationship marketing is a positive mediation variable on the relationship of service quality with loyalty. Customer satisfaction is also a positive mediation variable on marketing relationships with customer loyalty. Keywords: Service quality, Relationship marketing, Customer satisfaction, Customer loyalty, Bank BPR UMKM East Java JEL Classifications: L8, M31